OPTIMALISASI PEMANFAATAN LIMBAH AGROINDUSTRI SEBAGAI PAKAN TERNAK MELALUI SUPLEMENTASI KALSIUM DAN MAGNESIUM ORGANIK : PENGARUHNYA TERHADAP VFA DAN AMONIA CAIRAN RUMEN - Liza Novitha Sari; Muhtarudin .; Rudy Sutrisna (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2013)
This research aimed to determine the effects of Ca and Mg organic supplementation in agroindustrialby products based diets on VFA and Ammonia (NH3) concentration in goat rumen fluid.The research was conducted in October 2012 in the pen of Department of Animal Husbandry,Agriculture Faculty University of Lampung. Analysis of feed and rumen fluid samples performedat the Laboratory of Nutrition and Feed Science, Department of Animal Husbandry. This studyused a randomized block design which is consist of three treatments and three replications. Bodyweight as replicates and treatments used are R0 = Basal Rations (100%), R1 = Basal Rations(99,46%) + Ca Organic 0.50% + Mg Organic 0.04%, R2 = Basal Ration (98,92%) + Ca Organic1.00% + Mg Organic 0.08%. Analysis of variance is used to determine the effect of treatment,followed by least significant test at 5% significance level and or 1%. The results of this studyindicate that supplementation of organic minerals Ca and Mg was not significantly (P> 0.05) affectthe VFA and Ammonia (NH3) of goat rumen fluid.